Meninjau Keberlanjutan Perkebunan Kelapa Sawit Rakyat di Kabupaten Kolaka dan Kesiapaannya terhadap Implementasi Indonesian Sustainable Palm Oil (ISPO) - Prihantini, Campina Illa; Kartika, Kartika; Ningsih, Andi Wahda; Deeng, Antonio Brian; Ardiansyah, Moh. Iqbal; Masitah, Masitah; Rauf, Sugirah Hidayah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
A global issue concerning palm oil that is currently and will continue to develop is related to access to export markets or international trade. The international market, particularly the European Union, demands that the management and processing of palm oil plantations be responsible, taking into account social, environmental, and economic aspects. To be accepted in the international market, the palm oil produced must be sustainable and environmentally friendly. One government program to respond to this challenge is the development of the Indonesia Sustainable Palm Oil (ISPO) policy. Most independent smallholders have not yet implemented the ISPO policy. Kolaka Regency is one of the centers of palm oil production in Indonesia. This study aims to review the level of readiness for implementing sustainable palm oil certification in Kolaka Regency. This study focused on four main sub-districts: Tanggetada, Polinggona, Toari, and Watubangga. Involving 125 respondents from eight villages, the sample was selected using a multistage disproportionate purposive sampling method. The overall ISPO standard achievement among smallholders was 48.0%, indicating less sustainable management practices and partial readiness for certification, while also underscoring the need for continued capacity development to meet all mandatory ISPO criteria. The results of this study can be used as a set of indicators for the achievement of the 2020 regulation on ISPO implementation in Indonesia. These findings offer actionable evidence for stakeholders at the provincial and national levels to accelerate ISPO implementation and strengthen the sustainability performance of the Indonesian palm oil sector through improved extension, financing, and governance support for independent smallholders.